(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3GdHjVGhj, CHh SYjO, CHh GdNjQ, fGUQ GdOjf, YHO Gddg Hf YeQ Hf eMeO Hf Ydj(B685(3g`s ((3YHO GddWja Hf edG hdj GdbQHGZjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj fRd GdaQbGf Ydi YHOg djchf ddYGdejf fPjQG hHYO, aEf CYXe GdYdhe ebOGQG hCQaYgG TQaG Yde GdJaSjQ HCf CUfa aj gPG Gdaf cJGHG Cf CSejg (S0(3HCfhGQ GdJfRjd hCSQGQ GdJChjd(S1s
(3BNQgG (B:s
(3ef bQC ShQI Gdcga ef BNQgG cGfJ dg fhQG ef bQfg Edi bOeg, hef bQCgG cdgG cGfJ dg fhQG ef GdCQV Edi GdSeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 110s
(3eYLe GdeDdajf (B2 / 266s
(3cTa GdXfhf (B1 / 186s
(3TPQGJ GdPgH (B5 / 392s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs